Diffusion coefficients of CO2 and N-2 in water at temperatures between 298.15 K and 423.15 K at pressures up to 45 MPa - Cadogan,SP; Maitland,GC; Trusler,JPM (Journal of Chemical and Engineering Data, 2014)
We report measurements of the diffusion coefficients of CO2 and N2 in pure water at temperatures between (298.15 and 423.15) K and pressures between (15 and 45) MPa. The measurements were made by the Taylor dispersion method and have a standard relative uncertainty of 2.3 %. The results were found to be essentially independent of pressure over the range investigated and a simple relation, based on the Stokes–Einstein equation, is proposed to correlate the experimental data. Some experimental difficulties arising in the measurement of the diffusivities of slightly soluble acid-gas solutes such as CO2 in water are also discussed.